Productive and economic analyses of lowland soybean crops - Alves, Alexandre Ferigolo; Goin, Emerson José; Ribeiro, Bruna San Martin Rolim; Tagliapietra, Eduardo Lago; Inklman, Victória Brittes; Pilecco, Isabela Bulegon; Soares, Camille Flores; Streck, Nereu Augusto; Soares, Mauricio Fornalski; Zanon, Alencar Junior (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to estimate the relative yield that maximizes the profitability of the soybean crop in rotation with flood-irrigated rice. For this, 13 high-yield areas (from 2.6 to 5.2 ha) in lowland soybean-rice systems in Southern Brazil were selected before sowing. The calculation of production costs included seeds, seed treatment, fertilizers, lime, pesticides, irrigation, land, operational outsourcing, labor, and fuel consumption. The observed yield was transformed into relative yield by multiplying the quotient of the observed yield by the yield potential estimated by the CSM-CROPGRO-Soybean model. Water productivity was calculated as the ratio between the observed yield and available water during the crop cycle. Yield potential ranged from 6.1 to 7.4 Mg ha-1, whereas relative yield ranged from 45.3 to 101.2%. In addition, costs ranged from US564.86 to US1,122.86 per hectare, and profitability from US767.18 to US3,149.75 per hectare. The highest profitability of the soybean crop in rotation with flood-irrigated rice occurs with a relative yield between 67 and 84%.